The Emerging Role of Bioinformatics in Biotechnology - Tabassum Khan, Nida (Journal of Biotechnology and Biomedical Science, 2018)
Bioinformatic tools is widely used to manage the enormous genomic and proteomic data involving DNA/protein sequences management, drug designing, homology modelling, motif/domain prediction ,docking, annotation and dynamic simulation etc. Bioinformatics offers a wide range of applications in numerous disciplines such as genomics. Proteomics, comparative genomics, nutrigenomics, microbial genome, biodefense, forensics etc. Thus it offers promising future to accelerate scientific research in biotechnology
Keywords: CisML; Possum; Clover; SeqVISTA; WebGeSTer; GeneChords.